Co-developing a regional plan for preparedness and response to pest and disease outbreaks in West and Central Africa - Segnon, Alcade C.; Obossou, Esdras; Kpadonou, G. Esaïe; Ganyo, Komla Kyky; Lamien, Niéyidouba; Zougmoré, Robert B. (Accelerating Impacts of CGIAR Climate Research for Africa, 2023)
Climate change is a key driver of the spread of pests and diseases that affect food production in West and Central Africa. Science-policy linkages are essential for developing effective pests and disease management systems that can minimize agricultural losses to pests in Africa. With AICCRA support and engagement, a regional plan for preparedness and response to pest and disease outbreaks in West and Central Africa has been developed. The process of developing the regional plan was informed by a foresight analysis and is rooted in science-policy interaction based on multi-stakeholder consultation with local and regional experts. The plan will serve as a regional guide for holistic pest and disease management at regional, national, and sub-national levels.